Solution and Stability of Quartic Functional Equations in Modular Spaces by Using Fatou Property. (6th May 2022) - Uthirasamy, N.; Tamilvanan, K.; Nashine, Hemant Kumar; George, Reny
Abstract : We propose a novel generalized quartic functional equation and investigate its Hyers–Ulam stability in modular spaces using a fixed point technique and the Fatou property in this paper.